Pengaruh Iklim Psikologis Authentizotic, Stres Kerja dan Kebahagiaan Karyawan terhadap Intensi Turnover - Silverius Yoseph Soeharso; Yudith Christie (Jurnal Ilmiah Psikologi MIND SET, 2009)
This writing is intended to understand the factors which affecting intention of turnover. Spirit of camaraderie, trust and credibility of the leader, work-family conciliation, and opportunity for learning and personal development constitute an authentizotic psychology climate factors which circumstantially can affect intention of turnover. Stress at work and affective well-being will circumstantially affect the intention of turnover of employees. Analysis is conducted using Structural Equation Model (SEM). Through Confirmatory Factor Analysis it is found that all indicators are usable, except stress variable and affective well-being. It is concluded that 1) stress and affective well-being directly affect the intention of turnover of employees, and four authentizotic psychological climate factors circumstantially affect the intention of turnover, 2) the spirit of camaraderie gives no affect to employees affective well-being, 3) perception of employees to learning opportunity and developing into affect the affective well-being, 4) stress affects the affective well-being, 5) affective well-being affects the intention of turnover, 6) stress affects the intention of turnover, 7) perception of employees to a credible and reliable leader is significantly influential, 8) perception of employees to conciliation provided by the company in balancing between the job and family gives no effect to work stress.